Ruthenium complexes as inhibitors of human islet amyloid polypeptide aggregation, an effect that prevents beta cell apoptosis1. Issue 23 (13th March 2015) - Ma, Lijuan; Fu, Yuanting; Yu, Lianling; Li, Xiaoling; Zheng, Wenjie; Chen, Tianfeng
<x xml:space="preserve">Abstract</x> Herein we show that ruthenium complexes could inhibit fibrosis of hIAPP and protect the hIAPP-induced cell damage by suppressing ROS generation, indicating the application potential of the complexes in treatment of T2DM by targeting hIAPP.